2004
DOI: 10.1001/archpedi.158.2.170
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Reduce Television Viewing by Preschool Children

Abstract: This study is the first to show that a preschool-based intervention can lead to reductions in young children's television/video viewing. Further research is needed to determine the long-term effects associated with reductions in young children's television viewing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
274
8
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(291 citation statements)
references
References 20 publications
7
274
8
2
Order By: Relevance
“…[15][16][17]20,21 In the study (n ¼ 545) by Reilly et al 15 involving a 1-year intervention focused on reducing TV watching and increasing physical activity, no change in BMI z-score was observed in the intervention compared with the control group. In another small study, Dennisson et al 21 also did not find any significant effect of intervention targeting reduced television watching on BMI z-score compared with controls. However, in the study by Mo-Suwan et al 16 with 4 year olds, involving an intervention focused on increasing physical activity, a trend of reduction in prevalence of overweight was noted in the exercise versus control group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[15][16][17]20,21 In the study (n ¼ 545) by Reilly et al 15 involving a 1-year intervention focused on reducing TV watching and increasing physical activity, no change in BMI z-score was observed in the intervention compared with the control group. In another small study, Dennisson et al 21 also did not find any significant effect of intervention targeting reduced television watching on BMI z-score compared with controls. However, in the study by Mo-Suwan et al 16 with 4 year olds, involving an intervention focused on increasing physical activity, a trend of reduction in prevalence of overweight was noted in the exercise versus control group.…”
Section: Discussionmentioning
confidence: 97%
“…Few randomized controlled studies aiming at reducing overweight have been carried out with children o7 years of age. [13][14][15][16][17][18][19][20][21] In recent years, preschool age has been identified as a critical period for targeting interventions against obesity prevention. 22 Our goal was to evaluate interventions with young children that could be incorporated into existing schools, community and health-care programs, with physicians and community involvement, to optimize effectiveness and resources.…”
Section: Introductionmentioning
confidence: 99%
“…164 The other trials failed to show intervention effects on body composition, although several trials reported improvements in physical activity measures. [165][166][167][168][169][170][171][172] Three other reviews of randomized trials have been published, including 9 studies not previously reviewed. 129,173,174 Most of those studies were published before 2000; 8 were conducted in schools and 1 exclusively in the community.…”
Section: Physical Activity and Obesitymentioning
confidence: 99%
“…[9][10][11][12][13][14] Although some findings acknowledged only weak associations between sedentary behavior and obesity, limiting screen-related sedentary behaviors seems critical for preventing obesity. [15][16][17][18] Sedentary lifestyles are evident among young Canadian children; researchers have found that children aged 2 to 5 typically spend >3 hours each day watching television, exceeding the recommendation by up to 100%. 19,20 Early childhood interventions may promote lifelong healthy behaviors before the development of unhealthy behaviors.…”
Section: Introductionmentioning
confidence: 99%